2015
DOI: 10.1038/ncomms7658
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the TNF-α-induced phosphoproteome reveals AEG-1/MTDH/LYRIC as an IKKβ substrate

Abstract: The inhibitor of the nuclear factor-κB (IκB) kinase (IKK) complex is a key regulator of the canonical NF-κB signalling cascade and is crucial for fundamental cellular functions, including stress and immune responses. The majority of IKK complex functions are attributed to NF-κB activation; however, there is increasing evidence for NF-κB pathway-independent signalling. Here we combine quantitative mass spectrometry with random forest bioinformatics to dissect the TNF-α-IKKβ-induced phosphoproteome in MCF-7 brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 69 publications
(98 reference statements)
7
60
0
Order By: Relevance
“…Later, treatment with TNF-α showed to induces AEG-1 phosphorylation at Ser298 by the kinase IKKβ (210). Furthermore, TNF-α treatment or AEG-1 up-regulation increased the interaction with the NF-κB p65 subunit and nuclear translocation (198,204,205,210). We could confirmed the increased AEG-1 expression and translocation to the nucleolus upon TNF-α treatment in the SW480 cell line (unpublished data).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Later, treatment with TNF-α showed to induces AEG-1 phosphorylation at Ser298 by the kinase IKKβ (210). Furthermore, TNF-α treatment or AEG-1 up-regulation increased the interaction with the NF-κB p65 subunit and nuclear translocation (198,204,205,210). We could confirmed the increased AEG-1 expression and translocation to the nucleolus upon TNF-α treatment in the SW480 cell line (unpublished data).…”
Section: Resultssupporting
confidence: 73%
“…Class I proteins have the NH2-terminus exposed to the exterior site and the COOHterminal exposed to the cytoplasmic site, while it is the other way around for class II proteins (109,199 (109,(204)(205)(206)(207)(208). Furthermore, several post-translational modification sites were predicted, including phosphorylation, ubiquitination, and acetylation, while only the phosphorylation of AEG-1 at Ser298 was experimentally validated and showed biological significance (209,210).…”
Section: Astrocyte Elevated Gene-1 (Aeg-1)mentioning
confidence: 99%
“…More recently, a high-throughput screen combining quantitative MS with random forest bioinformatics to dissect the TNFα-IKKβ-induced phosphoproteome in MCF-7 breast cancer cells revealed dozens of potential IKKβ substrates (Krishnan et al 2015). Of significance, PFKFB3 phosphorylation was identified in this study, providing independent confirmation that PFKFB3 is a putative IKKβ substrate.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, AEG-1 knockdown in astrocytes exposed to IL-1β and TNF-α reduced NF-κB activation and signaling, suggesting that AEG-1 can be utilized as a target associated with astrocyte-mediated neuroinflammation (Vartak-Sharma et al , 2014). This observation is further supported by a recent phosphoproteomics study conducted in breast cancer cells, wherein it was demonstrated that AEG-1 is a direct target of IKKβ at serine 298 and that AEG-1 phosphorylation is essential for IκBα degradation, as well as, NF-κB-dependent gene expression (Krishnan et al , 2015). …”
Section: Aeg-1 In Handmentioning
confidence: 60%